Chemical Constituents from the Stems of Daphne holosericea (Diels) Hamaya. Issue 11 (8th October 2016) - Ma, Qing‐Yun; Chen, Yi‐Chun; Huang, Sheng‐Zhuo; Kong, Fan‐Dong; Zhou, Li‐Man; Dai, Hao‐Fu; Hua, Yan; Zhao, You‐Xing
Abstract : Two new compounds, one flavanol dimer dapholosericol A (1 ) and one tigliane diterpene dapholosericin A (2 ), together with ten known ones, were isolated from the AcOEt extract of Daphne holosericea (Diels )Hamaya . Their structures were elucidated by their spectroscopic data analysis. Compounds1 and2 showed moderate activities against acetylcholinesterase with inhibition ratio of 36% and 29% at a concentration of 100 μmol/l, respectively. Abstract :